2007
DOI: 10.1093/bja/aem230
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of bilateral superficial cervical plexus block administered before thyroid surgery under general anaesthesia

Abstract: BSCPB with ropivacaine and clonidine improved intraoperative analgesia. BSCPB with ropivacaine or ropivaciane and clonidine was effective in reducing analgesic requirements after thyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 21 publications
2
82
1
7
Order By: Relevance
“…All BSCPB administrations were performed by the same anaesthesia team after intubation using the same technique. Three-point injection technique was used for block administration (8). With this technique, after the head is turned facing the other side, a 22-gauge injector is inserted on the mid-point of the back verge of the sternocleidomastiod muscle, the injector is directed caudally, cephalically and horizontally (from sternocleidomastiod muscle) and 10 mL of 0.5% levobupivacaine hydrochloride (Chirocaine ® 0.5%, Abbot…”
Section: Approval Of Ethics Committee Was Received From 19mentioning
confidence: 99%
“…All BSCPB administrations were performed by the same anaesthesia team after intubation using the same technique. Three-point injection technique was used for block administration (8). With this technique, after the head is turned facing the other side, a 22-gauge injector is inserted on the mid-point of the back verge of the sternocleidomastiod muscle, the injector is directed caudally, cephalically and horizontally (from sternocleidomastiod muscle) and 10 mL of 0.5% levobupivacaine hydrochloride (Chirocaine ® 0.5%, Abbot…”
Section: Approval Of Ethics Committee Was Received From 19mentioning
confidence: 99%
“…Blok uygulamasında üç nokta enjeksiyon tekniği kullanılmıştır. 9 Bu teknikle baş karşı tarafa çevril-dikten sonra, 22 gauge iğne ile sternokleidomastoid kasın arka sınırının orta noktasından girip, iğne kaudale, sefaliğe ve horizontal (sternokleidomastoid kasının üzerinden) yönlendirilerek maksimum 1 cm derinlikte olacak şekilde boynun her iki tarafına 10'ar ml %0,5 levobupivakian infiltre edilmiş-tir.…”
Section: Gereç Ve Yöntemlerunclassified
“…Bilateral superficial cervical plexus block (BSCPB) is reported to reduce postoperative pain and analgesic requirements after adult thyroid and carotid surgery. [1][2][3] Bilateral superficial cervical plexus block may also reduce postoperative analgesic requirements in children undergoing ear surgery. 4,5 A review of our experience with cochlear implantation identified a greater postoperative opioid consumption in children undergoing bilateral simultaneous cochlear implantation (BSiCI) when compared with children undergoing unilateral implants, and a suspicion arose that the greater analgesic requirement was a reflection of increased postoperative pain.…”
Section: Résumémentioning
confidence: 99%